Phytochemical and biological activity screening of the crude extracts of Ficus ampelas (Fam. Moraceae) and Wrightia spp. (Fam. Apocynaceae) - Salud, Arnold M.; Suguitan, Anthony A. (2005)
The dried dichloromethane (DCM) and methanol extracts of Ficus ampelas (Fam. Moraceae) and Wrightia spp. (Apocynaceae) were subjected to phytochemical screening which showed that the methanolic extract of F. ampelas contains glycosides and reducing substances while in the methanolic extract of Wrightia, the presence of tannins, glycosides, reducing substances, and flavonoids were indicated. The DCM extracts of both plants showed negative results in all the phytochemical tests performed. The extracts were also investigated for biological activity, namely, lethality to brine shrimp, and antimicrobial activity using methods such as disk diffusion assay, minimal inhibitory concentration (MIC) determination, and contact bioautography. In the brine shrimp lethality assay, the DCM extract of Wrightia sp. showed the highest mortality rate, which was 97%. The LC50 of this extract was determined which was 48.48 mg/mL. In the disk diffusion assay, the methanolic extract of F. ampelas produced a zone of inhibition against S. aureus measuring 15.55 mm. The MIC of this extract was 850 mg/mL. The methanolic extract of Wrightia sp. On the other hand produced zones of inhibition measuring 9.5 mm in S. aureus, E. aerogenes, and P. vulgaris, 9.0 mm in E. coli, and 8.0 mm in K. pneumoniae. The determined MIC of this extract was 200 mg/mL. None of the DCM extracts produced zones of inhibition. Contact bioautography was done using chloroform-methanol (89:11 for F. ampelas. 80:20 for Wrightia sp.) as solvent system. Zones of inhibition were observed in certain areas of the chromatogram
Thesis (B.S. Pharmacy)--University of the Philippines Manila.
Keywords: Ficus (Plants); Moraceae; Apocynaceae